Description of Infection Control Prevention Program in the Internal Room of Aloei Saboe Hospital, Gorontalo City - Sabirin B Syukur; Rini Asnawati; Moh. Sudirman Mustapa; Siti Rahma Binol; Nurdawati Lajambu; Ni'ma Chusnul Chatimah; Nolva Laiya (Journal La Medihealtico, 2022)
Infection Prevention and Control (PPI) is an effort to prevent and minimize the occurrence of infections in patients, staff, visitors and the community around health care facilities. Nosocomial infection control is an activity of planning, implementing, monitoring, and fostering with the aim of reducing the incidence of nosocomial infections. The purpose of this study was to determine the description of infection prevention and control in the internal room of the Prof. Dr. Aloei Saboe Gorontalo City. This study used a qualitative descriptive research method with a sample of 15 respondents obtained using random sampling technique. The results showed that the infection prevention and control program in the internal room had not been fully implemented, seen from 15 participants there were 3 people who did not practice handwashing properly where the 3 respondents did not apply the 6 steps of hand washing according to the SOP, there was 1 person who did not using PPE in the procedure, overall able to apply coughing and sneezing etiquette, there was 1 person who did not apply safe injection practices in the procedure.overall able to apply Decontamination of equipment after completion of actions.